EFEKTIVITAS PENGALIHAN DANA DEKONSENTRASI DAN TUGAS PEMBANTUAN KE DANA ALOKASI KHUSUS - Wahyu Dede Kusuma; Viki Anggraini Soeprapto (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2018)
In accordance with the mandate of Law No. 33 of 2004 and Government Regulation No. 7 of 2008, deconcentration and co-administration funds (Dekon TP funds) will be gradually transferred to the special allocation fund (DAK). Some activities that are regional affairs should be carried out by the regions through special allocation funds. This study is focused on the budget contained in the Ministry of Agriculture. The agricultural sector was chosen as a case study because it was a new initiative to make the matter to be authority of the local government. This study tries to analyze three things, namely: (1) how the regional responses to diversion policies; (2) how diversion readiness is through a performance evaluation perspective approach; and (3) how the effectiveness of Deconcentration Funds, Co-Administration Tasks and Special Allocation Funds on the performance of the agricultural sector at the national level. Based on the analysis that has been carried out using the Analytical Hierarchy Process (AHP) and Vector Autoregression (VAR) methods, the following conclusions are obtained: (1) from the perspective of performance evaluation measurement shows that the regional perspective and DJA place greater benefits in the assessment compared to the implementation aspect budget, it means that the region has preparedness in the transfer of responsibility along with the transfer of funding, (2) readiness of transfering Dekon TP funds to DAK by using budget performance evaluation, and (3) in terms of the effectiveness of the agricultural sector performance, there is no strong evidence to illustrate that special allocation funds, deconcentration funds and co-administration are effective in increasing farmer welfare. Abstrak Sesuai dengan amanat dari Undang-undang Nomor 33 Tahun 2004 dan PP Nomor 7 Tahun 2008, dana dekonsentrasi dan tugas pembantuan (dana Dekon TP) akan dialihkan ke dana alokasi khusus (DAK) secara bertahap. Beberapa kegiatan yang menjadi urusan daerah sudah seharusnya dilaksanakan oleh daerah melalui dana alokasi khusus. Kajian ini difokuskan pada anggaran yang terdapat di Kementerian Pertanian. Sektor pertanian dipilih sebagai studi kasus karena merupakan inisiatif baru untuk menjadikan urusan tersebut menjadi wewenang dari pemerintah daerah. Kajian ini mencoba menganalisis tiga hal, yaitu: (1) bagaimana tanggapan daerah terhadap kebijakan pengalihan; (2) bagaimana kesiapan pengalihan melalui pendekatan perspektif evaluasi kinerja; dan (3) bagaimana efektivitas Dana Dekonsentrasi, Tugas Pembantuan, dan Dana Alokasi Khusus terhadap kinerja sektor pertanian di level nasional. Berdasarkan analisis yang telah dilakukan dengan menggunakan metode Analytical Hierarchy Process (AHP) dan Vector Autoregression (VAR) diperoleh kesimpulan sebagai berikut: (1) dari perspektif pengukuran evaluasi kinerja menunjukan bahwa perspektif daerah dan DJA menempatkan aspek manfaat lebih besar dalam penilaian bila dibandingkan aspek implementasi anggaran, artinya daerah telah memiliki kesiapan dalam pengalihan tanggung jawab seiring pengalihan pendanaan, (2) kesiapan pengalihan dekon TP ke DAK dengan pendekatan evaluasi kinerja anggaran, dan (3) dari sisi efektivitas kinerja sektor pertanian, belum ada bukti yang kuat untuk menggambarkan bahwa dana alokasi khusus, dana dekonsentrasi dan tugas pembantuan efektif dalam meningkatkan nilai tukar petani.